2021
DOI: 10.1111/exd.14382
|View full text |Cite
|
Sign up to set email alerts
|

Current views on neuropeptides in atopic dermatitis

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease involving skin barrier dysfunction and immune imbalance. However, the mechanism of AD is not clear completely and may be related to heredity and environment. Neuropeptides are a class of peptides secreted by nerve endings, they may play roles in promoting vasodilation, plasma extravasation, chemotaxis of inflammatory cells and mediating pruritus. Since itching and immune cell infiltration are the main manifestations of atopic dermatitis, to further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 127 publications
0
6
0
Order By: Relevance
“…Alexithymia may also be linked to altered immune responses. In susceptible individuals, neuroimmune substances, such as neuropeptides, triggered by stress, can lead to increased cutaneous inflammation, an impaired epidermal barrier, and increased itch [ 54 , 55 , 58 ]. Guilbaud et al hypothesised that alexithymia may physiologically resemble a chronic stress condition with up-regulated T helper 2 (T H 2) and impaired T helper 1 (T H 1) responses, while individuals remain emotionally unaware of their true distress [ 57 ].…”
Section: Mental Health Conditions Associated With Admentioning
confidence: 99%
“…Alexithymia may also be linked to altered immune responses. In susceptible individuals, neuroimmune substances, such as neuropeptides, triggered by stress, can lead to increased cutaneous inflammation, an impaired epidermal barrier, and increased itch [ 54 , 55 , 58 ]. Guilbaud et al hypothesised that alexithymia may physiologically resemble a chronic stress condition with up-regulated T helper 2 (T H 2) and impaired T helper 1 (T H 1) responses, while individuals remain emotionally unaware of their true distress [ 57 ].…”
Section: Mental Health Conditions Associated With Admentioning
confidence: 99%
“…Moreover, in vivo, increased levels of TSLP work directly on CD4+ T cells to cause the establishment of IL-13-single-positive (IL-13-SP) and IL-4+IL-13+ double-positive populations in lymph nodes modifying the function of immune system [43]. Harmful stimuli and stress via, for instance, upraised levels of nerve growth factor (NGF), can uprise the amount of nerve fibres that secrete neuropeptides such as neuropeptide Y (NPY), substance P, calcitoningene regulated peptide (CGRP), or brain natriuretic peptide (BNP) [44]. These factors regulate the function of various inflammatory cells including mast cells and release of cytokines [44].…”
Section: Neurologic and Psychiatric Diseases In Admentioning
confidence: 99%
“…Harmful stimuli and stress via, for instance, upraised levels of nerve growth factor (NGF), can uprise the amount of nerve fibres that secrete neuropeptides such as neuropeptide Y (NPY), substance P, calcitoningene regulated peptide (CGRP), or brain natriuretic peptide (BNP) [44]. These factors regulate the function of various inflammatory cells including mast cells and release of cytokines [44].…”
Section: Neurologic and Psychiatric Diseases In Admentioning
confidence: 99%
“…Importantly, activated sensory neurons, in turn, could release neuropeptides or transmitters that act on mast cells to form a neuroimmune feedback loop. It has been demonstrated that mast cells have several receptors for neuropeptides, such as substance P (SP), calcitonin-gene-related peptide (CGRP), neuropeptide Y (NPY), and vasoactive intestinal peptide (VIP), expressed on their surface [ 28 ]. Decades ago, mast cells were discovered to degranulate in response to nerve growth factor (NGF) by the TrkA tyrosine receptor [ 29 ].…”
Section: Atopic Dermatitis (Ad): a Paradigm Of Itch Neuroimmune Mecha...mentioning
confidence: 99%